2017
DOI: 10.18553/jmcp.2017.23.12.1214
|View full text |Cite
|
Sign up to set email alerts
|

Conversion from Filgrastim to Tbo-filgrastim: Experience of a Large Health Care System

Abstract: No outside funding supported this study. Agboola was employed by Partners Healthcare at the time of the study. The authors have nothing to disclose. Study concept and design were contributed equally by Agboola and Reddy. Agboola collected the data, and data interpretation was performed by both authors. The manuscript was written primarily by Agboola, with assistance from Reddy. Both authors revised the manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 14 publications
(25 reference statements)
0
11
0
Order By: Relevance
“…A study by Grabowski et al reported that Sweden and Germany observed fast uptake of a filgrastim biosimilar, while Italy, France, and the United Kingdom lagged behind [9]. Uptake can also be highly variable even within a single healthcare system, as one study observed that 90% of inpatients in eastern Massachusetts used the biosimilar tbo-filgrastim, compared to only 50% of outpatients [10]. It is unsurprising that biosimilars have not been able to penetrate the Canadian market as generic drugs do, given their complexity, lack of interchangeability, and lower discounting than in other countries [3].…”
Section: Discussionmentioning
confidence: 99%
“…A study by Grabowski et al reported that Sweden and Germany observed fast uptake of a filgrastim biosimilar, while Italy, France, and the United Kingdom lagged behind [9]. Uptake can also be highly variable even within a single healthcare system, as one study observed that 90% of inpatients in eastern Massachusetts used the biosimilar tbo-filgrastim, compared to only 50% of outpatients [10]. It is unsurprising that biosimilars have not been able to penetrate the Canadian market as generic drugs do, given their complexity, lack of interchangeability, and lower discounting than in other countries [3].…”
Section: Discussionmentioning
confidence: 99%
“…While biosimilar products are highly similar to their reference product, they are not currently considered interchangeable and cannot be substituted without intervention of the prescriber [71]. Furthermore, it is important to note that tbo-filgrastim was approved in Europe as a biosimilar in 2008; however, in the United States, it was approved in 2012 as a biologic product because it was filed under a Biologics License Application since the biosimilars pathways was not established at the time of FDA submission [72].…”
Section: Current Strategies To Prevent and Treat Cin And Improve Rdimentioning
confidence: 99%
“…4,5 Previous publications have described barriers to biosimilar uptake. 6,7 Despite there being no expected difference in effectiveness between a biosimilar and its originator product, prescribers have limited comfort and confidence when biosimilars enter the market. 6,8 This lack of uptake may be more discernible when products are being prescribed for "at-risk" patient populations, for which there is a lack of data in the studies submitted for approval of the biosimilars.…”
Section: Introductionmentioning
confidence: 99%